changed my unit_M to Chris' convention of M_unit, for consistency
[lambda.git] / hints / assignment_4_hint_3_alternate_1.mdwn
1 Alternate strategy for Y1, Y2
2
3 *       This is (in effect) the strategy used by OCaml. The mutually recursive:
4
5                 let rec
6                         f x = A  ; A may refer to f or g
7                 and
8                         g y = B  ; B may refer to f or g
9                 in
10                         C
11
12         is implemented using regular, non-mutual recursion, like this (`u` is a variable not occurring free in `A`, `B`, or `C`):
13
14                 let rec  u g x = (let f = u g in A)  in
15                 let rec    g y = (let f = u g in B)  in
16                 let                   f = u g        in
17                 C
18
19         or, expanded into the form we've been working with:
20
21                 let u =    Y (\u g. (\f x. A) (u g))  in
22                 let g =    Y (  \g. (\f y. B) (u g))  in
23                 let f =                        u g    in
24                 C
25
26         We could abstract Y1 and Y2 combinators from this as follows:
27
28                 let Yu = \ff.    Y (\u g. ff ( u      g        ) g)  in
29                 let Y2 = \ff gg. Y (  \g. gg (Yu ff   g        ) g)  in
30                 let Y1 = \ff gg.             (Yu ff) (Y2 ff gg)      in
31                 let f  = Y1 (\f g. A) (\f g. B)  in
32                 let g  = Y2 (\f g. A) (\f g. B)  in
33                 C
34
35
36 *       Here's the same strategy extended to three mutually-recursive functions. `f`, `g` and `h`:
37
38                 let v = Y (\v g h.      (\f x. A) (v g h)) in
39                 let w = Y (  \w h. (\g. (\f y. B) (v g h)) (w h)) in
40                 let h = Y (    \h. (\g. (\f z. C) (v g h)) (w h)) in
41                 let g =                                     w h in
42                 let f =                            v g h in
43                 D
44
45         <!--
46         Or in Y1of3, Y2of3, Y3of3 form:
47
48                 let Yv    = \ff.       Y (\v g h.      ff ( v    g h) g h)                in
49                 let Yw    = \ff gg.    Y (  \w h. (\g. gg (Yv ff g h) g h) ( w       h))  in
50                 let Y3of3 = \ff gg hh. Y (    \h. (\g. hh (Yv ff g h) g h) (Yw ff gg h))  in
51                 let Y2of3 = \ff gg hh.                                      Yw ff gg (Y3of3 ff gg hh)  in
52                 let Y1of3 = \ff gg hh.                     Yv ff (Y2of3 ff gg hh) (Y3of3 ff gg hh)     in
53                 let f = Y1of3 (\f g h. A) (\f g h. B) (\f g h. C)  in
54                 let g = Y2of3 (\f g h. A) (\f g h. B) (\f g h. C)  in
55                 let h = Y3of3 (\f g h. A) (\f g h. B) (\f g h. C)  in
56                 D
57         -->
58